Interplay between Light and Plant Hormones in the Control of Arabidopsis Seedling Chlorophyll Biosynthesis - Liu, Xiaoqin; Li, Yue; Zhong, Shangwei (Frontiers in Plant Science, 2017)
Chlorophyll biosynthesis is one of the most important cellular processes and is essential for plant photosynthesis. After germination under the soil, dark-grown seedlings are etiolated and accumulate the chlorophyll precursor protochlorophyllide (Pchlide) in cotyledons. Upon exposure to light, Pchlide is rapidly converted to chlorophyll to initiate photoautotrophic growth. In this light-regulated de-etiolation process, multiple endogenous phytohormones are also involved. Although the co-regulation of seedling greening by light and hormones has long been observed, recent studies greatly advanced our understanding of their interplay by identifying the key components connecting these pathways. The integrators, such as PHYTOCHROMEINTERACTING FACTORs (PIFs), ELONGATED HYPOCOTYL 5 (HY5), ETHYLENE INSENSTIVE 3 (EIN3) and DELLA proteins, are key transcription regulators in light or hormone signaling pathways. This review focuses on these integrators and illustrates the regulatory networks of light and hormone interactions in chlorophyll biosynthesis.